2007
DOI: 10.12968/hmed.2007.68.6.23582
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled heroin causing a life-threatening asthma exacerbation and marked peripheral eosinophilia

Abstract: Miss H was born in 1982 and diagnosed with asthma at the age of 7 years. In 2004 she presented with cough and wheeze, a peak flow of 55% predicted, an eosinophil count of 3.75 × 109/litre (normal range 0−0.4 × 109/litre) and a normal chest radiograph. In the preceding year, she attended the accident and emergency department twice and required six courses of prednisolone, despite taking low-dose inhaled steroids on a regular basis. A smoker, she lived in a rented room and was not registered with a doctor. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The immune system is important for opioid users because the individuals with heroin use are in a high-risk group for the development of infectious diseases such as HIV and Hepatitis B and C as much as this addiction itself is a chronic disease causing numerous complications including alterations in immune responses [9, 10]. These functional alterations caused by opioids in immune cell functions have been investigated since the 1970s [11].…”
Section: Introductionmentioning
confidence: 99%
“…The immune system is important for opioid users because the individuals with heroin use are in a high-risk group for the development of infectious diseases such as HIV and Hepatitis B and C as much as this addiction itself is a chronic disease causing numerous complications including alterations in immune responses [9, 10]. These functional alterations caused by opioids in immune cell functions have been investigated since the 1970s [11].…”
Section: Introductionmentioning
confidence: 99%
“…Especially the common view that substance abuse by inhalation was less harmful than the IV mode among substance abusers has recently led to an increase in substance abuse through inhalation [11,12]. The results of our study showed that both heroin and cocaine were most commonly abused through inhalation and the rate of this mode of abuse was significantly higher than that of the IV mode.…”
Section: Discussionmentioning
confidence: 54%
“…Irritation et inflammation non spécifique des voies aériennes L'irritation et l'inflammation non spécifique des voies aériennes liées à la consommation d'héroïne provoquent une HRB, une bronchoconstriction et une majoration de l'inflammation bronchique préexistante. Plusieurs facteurs peuvent être en cause : agression thermique des voies aériennes par les vapeurs dégagées lors de la combustion, irritation de la muqueuse bronchique par les impuretés et/ou les agents de coupe de la poudre d'héroïne [4,5,37,65].…”
Section: Mécanisme Allergiqueunclassified